Teaching about Technology An Introduction to the Philosophy of Technology for Non-philosophers - de Vries, Marc J. (Contemporary Issues in Technology Education, 2016)
This book provides an introduction to the philosophy of technology. It offers a survey of the current state-of-affairs in the philosophy of technology, and discusses its relevance for teaching about technology. Teaching about technology, at all levels of education, can only be done properly when those who teach have a clear idea about what it is that they teach. In other words: they should be able to give an appropriate answer to the question: what is technology? The question of the nature of technology is explored in the philosophy of technology, making this a highly relevant discipline for those who teach about technology. Literature in this field, however, is not always easy to access for non-philosophers. By providing an introduction to the philosophy of technology, this book makes the discipline more easily accessible. The book can be used in introductory courses on the philosophy of technology in teacher education programs, engineering education programs, and by individual educators who are interested in the intriguing phenomenon of technology that is so important in our contemporary society.